The effect of sequencing trade and water market reform on interest groups in irrigated agriculture: an intertemporal economy-wide analysis of the Moroccan case - Diao, Xinshen; Roe, Terry L. (University of Minnesota, 1998)
Using an intertemporal general equilibrium model, the paper analyzes the economy-wide effects of the linkages between trade reform and the reform of water markets in irrigated agriculture